Measurement of the aerodynamic forces acting on a non-spinning javelin using an MSBS - Kobayashi, T.; Seo, K.; Kaneda, S.; Sasaki, K.; Shinji, K.; Oyama, S.; Okuizumi, H.; Konishi, Y.; Hasegawa, H.; Obayashi, S. (Proceedings, 2020)
Using the world`s largest magnetic suspension and balance system (MSBS) and a low-turbulence wind tunnel, we successfully measured the aerodynamic forces acting on a non-spinning women`s javelin. It was found that the drag and the lift increased as the angle of attack was increased up to 18°. The pitching moment increased for angles of attack up to about 9°, and then decreased, becoming negative above 12°, indicating nose-down rotation. We used a pseudo supporting rod to simulate a javelin attached to a support, as used in a conventional setup, and confirmed that this interferes with the javelin by creating differences between the aerodynamics forces acting on the javelin with and without the pseudo supporting rod.